2010
DOI: 10.1002/smll.201001349
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Influenza Virus Infection by Multivalent Sialic‐Acid‐Functionalized Gold Nanoparticles

Abstract: An efficient synthesis of sialic-acid-terminated glycerol dendron to chemically functionalize 2 nm and 14 nm gold nanoparticles (AuNPs) is described. These nanoparticles are highly stable and show high activity towards the inhibition of influenza virus infection. As the binding of the viral fusion protein hemagglutinin to the host cell surface is mediated by sialic acid receptors, a multivalent interaction with sialic-acid-functionalized AuNPs is expected to competitively inhibit viral infection. Electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
215
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 280 publications
(223 citation statements)
references
References 37 publications
5
215
0
3
Order By: Relevance
“…High molecular‐weight scaffolds displaying a large number of low affinity SA derived ligands were used to achieve high HA avidity. Over the years several carrier systems were employed as scaffolds ranging from polymers,6, 8, 9 dendrimers,10, 11, 12, 13 liposomes,5, 14 proteins,15 to gold nanoparticles 16. The most affine binders reported to date consist of SA tethered to linear polyacrylamide polymers 6.…”
mentioning
confidence: 99%
“…High molecular‐weight scaffolds displaying a large number of low affinity SA derived ligands were used to achieve high HA avidity. Over the years several carrier systems were employed as scaffolds ranging from polymers,6, 8, 9 dendrimers,10, 11, 12, 13 liposomes,5, 14 proteins,15 to gold nanoparticles 16. The most affine binders reported to date consist of SA tethered to linear polyacrylamide polymers 6.…”
mentioning
confidence: 99%
“…As the binding of the viral fusion protein hemagglutinin to the host cell surface is mediated by sialic acid receptors, a multivalent interaction with sialic-acidfunctionalized NPs is expected to competitively inhibit viral infection. 89 The diverse functional possibilities of NCDs allows for a variety of approaches for nanocarriers design (see Figure 4). Fox et al reported the synthesis of water soluble Au NCDs that exhibit micellar properties capable of encapsulating pinacyanol chloride.…”
Section: Performance Of Ncds In Bionanomedicine and As Nanocarriers Imentioning
confidence: 99%
“…Bindung von Viruspartikeln an Nanopartikeln [80,81] Fluoreszenzmikroskopie Fluoreszenzintensität als Funktion der Zeit Geschwindigkeitskonstante Bindung von CdS-Quantenpunkten mit variabler Ligandenmultivalenz an GABA(C)-Rezeptoren auf einer Zellmembran [82] dynamische Lichtstreuung (DLS) hydrodynamischer Durchmesser (aus zeitlicher ¾nderung der Streuintensität) als Funktion der Zeit Aggregationsgeschwindigkeitskonstante (Maß für Stabilität gegen Aggregation infolge multivalenter Stabilisierung…”
Section: Stabilität Gegen Aggregation Als Funktion Multivalenter Stabunclassified